METHODS USED TO JUSTIFY STRATEGIES OF ACHIEVING THE EXPANDED POPULATION REPRODUCTION - Tikhomirov, Nikolay; Tikhomirova, Tatiana (Revista Inclusiones, 2020)
Approaches and methods for solving the problems of justifying the directions and measures of the socioeconomic policy that contribute to the transition of the population in some European states and Russia from the established depopulation mode to sustainable reproduction have been discussed in this article. The indicators that are independent of the age and sex population structure have been proposed; they are the indicators that objectively and unambiguously describe the reproduction mode established in the current period and predetermined only by the levels of the age and sex birth and death rates. The main attention among them is paid to the marginal and standardized population growth rates. The methods for assessing these indicators and the characteristics of their sensitivity to changes in age and sex rates of natural motion ratios have been described. The prevailing importance of the age-specific fertility rate growth in comparison with the reduction in the death rate for the transition to the expanded population reproduction has been justified. The methods have been proposed for estimating the growth of the age-specific fertility rates, which ensure the transition of the population from the current reproduction mode to the expanded mode.